Pelestarian Naskah-naskah Kuno di Museum Nagari Adityawarman Sumatera Barat - Riko Gusmanda; Malta Nelisa (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purpose of this paper is to describe about: (1) whether the cause of preservation of ancient manuscripts in the Museum Nagari less attention Adityawarman, (2) whether the effort to preserve the ancient manuscripts in the Museum Nagari Adityawarman. Data were collected through observation and interviews with staff-staff at the Museum Nagari Adityawarman. Analyzing data descriptively. By analyzing the data, it was concluded the following things: first factors that may cause less noticeable preservation of ancient manuscripts in the Museum Nagari Adityawarman, namely: (1) the absence of a special schedule for the preservation of ancient manuscripts, the museum only do conservation if there is free time alone in the absence of a structured schedule. (2) human resources or manpower to inadequate preservation activities in the conduct of preservation of ancient manuscripts. (3) in the absence Adityawarman Museum Nagari specific budget for these activities, so that conservation is rarely done. (4) preservation of infrequently used rooms. In the museum there is a special room Nagari Adityawarman for preservation and conservation. In the room there are tools to do conservation. However, the room is rarely used in preservation. Both efforts in preserving ancient manuscripts in the Museum Nagari Adityawarman, namely: (1) provide a box for text files and compiled on the shelf. And given a classification number in each box file, for easy in and easy shelves in preparation of the manuscript rediscovered required. (2) in cooperation with the National Library to carry out activities on the fumigation of ancient texts, but it will take quite a long time. (3) improve the manuscript is torn by patched with another paper on damaged script, then coat it with wax paper or often also called Japanese paper (Gokayama), to reinforce durability without losing information contained in the text. Keywords: museum; manuscripts; preservation